Strategi Pemasaran Soe Studio Jombang Melalui Marketing Mix 4p Guna Meningkatkan Keputusan Pembelian - Rizky Amalia; Nugroho, Rusdi Hidayat (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The increasingly sophisticated development of world technology means that all countries in the world must be able to keep up with the times. One area that is currently being intensively developed is the economic sector. The development of the Indonesian economy is currently experiencing quite a significant increase. MSMEs are one of the economic sectors that have an important role in the development of the Indonesian economy. Before going any further, every company must determine the marketing strategy that will be used to run its business. This research aims to help Soe Studio Jombang MSMEs to analyze the application of the 4P marketing mix to Soe Studio Jombang consumer purchasing decisions. In this research, the type of research used is associative research with a quantitative approach. The population and sample in this research are Soe Studio Jombang consumers with a population of 1,500 with ages <25 years - >45 years. The sampling technique used in this research was nonprobability sampling with a purposive sampling method. The types of data used in this research are primary data and secondary data. The data collection method in the research used a questionnaire. The analysis technique used was multiple linear regression analysis. The research results show that the F test calculation simultaneously shows that the significant value is 0.000 < 0.05 and the calculated F value is 39.854 > F table 2.466, meaning there is an influence on purchasing decisions. In the partial t test calculation, it is known that the Sig value for the influence of X1 on Y is 0.000 < 0.05 and the calculated t value is 4.777 > t table 1.985 so it can be concluded that there is an influence. The Sig value for the influence of X2 on Y is 0.823 > 0.05 and the calculated t value is -0.225 < t table 1.985 so it can be concluded that there is no influence. The Sig value for the influence of X3 on Y is 0.000 < 0.05 and the calculated t value is 5.845 > t table 1.985 so it can be concluded that there is an influence. The Sig value for the influence of X4 on Y is 0.715 > 0.05 and the t value is 0.715 < t table 1.985 so it can be concluded that there is no influence. Simultaneously the independent variables product, price, promotion, place have a significant effect on the dependent variable on purchasing decisions. Partially, the independent variable product has a significant effect on the dependent variable on purchasing decisions. Partially, the independent variable price does not have a significant effect on the dependent variable on purchasing decisions. Spatially, the independent variable promotion has a significant effect on the dependent variable on purchasing decisions. Partially, the independent variable place has no significant effect on the dependent variable on purchasing decisions.